Preparing for Digital Learning Monitoring in the Fraction Context: Assessment of Students’ Prior Knowledge According to Evidence-Based Cognitive Models - Schadl, Constanze; Lindmeier, Anke (International Journal of Science and Mathematics Education, 2025)
Regularly assessing students’ learning using evidence-based cognitive models can enhance learning by supporting teachers’ monitoring and scaffolding decisions. In the case of mathematics, this is considered especially essential for topics renowned as being complex for students, like fractions. Although previous findings from paper-based studies yielded sophisticated cognitive models, they were not consistently related so far to evidence-based assessment approaches. Also, as paper-based testing appears resource-consuming, its practical use is hindered. Addressing this gap, we developed instruments for digital evidence-based assessment. This paper focuses on the psychometric quality of two tests assessing prior knowledge of fractions: symbolic multiplication and division skills (SMDS) and proportional reasoning skills (PRS). Using item-response-theory-methods to analyze data from N = 147 fifth graders, the digital SMDS-test showed good reliability and validity. The findings suggest a specific item subset suited as an efficient short test. Regarding PRS, further adaptation of the digital format is advised.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Cognitive model; Evidence-based digital assessment; Item-response-theory-methods; Proportional reasoning skills; Symbolic multiplication and division skills